Interacting Quintessence Dark Energy Models in Lyra Manifold - M. Khurshudyan; J. Sadeghi; R. Myrzakulov; Antonio Pasqua; H. Farahani (Advances in High Energy Physics)
We consider two-component dark energy models in Lyra manifold. The first component is assumed to be a quintessence field while the second component may be a viscous polytropic gas, a viscous Van der Waals gas, or a viscous modified Chaplygin gas. We also consider the possibility of interaction between components. By using the numerical analysis, we study some cosmological parameters of the models and compare them with observational data.